Dysfunctional of Leader - Member Exchange (LMX) Theory - Azlawati, Fahmi (2009)
Leader-member exchange (LMX) theory was initially called the vertical dyad linkage theory. Graen and Cashman introduced it in 1975. It emphasizes on the dyadic relationships between leaders and individual subordinates, instead of the traits or behaviors of leaders or situational characteristics. According to LMX theory, leaders do not treat all subordinates in the same manner, but establish close relationships with some (the in-group) while remaining aloof from others (the out-group). Therefore, this study is intended to examine the perception of out-group members in relation to favoritism, impression management tactics, perception of inequity and member-member exchange (MMX). The respondents of the study are 95 middle managers in the SUK, Shah Alam, Selangor Darul Ehsan. The study found that members do not have perception of injustice when they see in-group members as relying on the use of impression management tactics to gain inclusion into the in-group. There is no positive relationship between favoritism and perception of inequity. Similarly, favoritism does not lead to lower MMX. The result also found that perception of injustice does not mediate the relationship between LMX of in-group members and MMX. On the other hand, the study found that level of MMX is affected by LMX. Level of MMX is also affected by perception of justice. Since research on dysfunctional LMX is hardly been attempted in Malaysia, it is interesting to further explore this subject in different context and in a larger scale. Future research may expand the LMX theory developed.